Dissection of the CAR1 UASI regulatory sequences responsible for induced expression of the arginase gene in Saccharomyces cerevisiae - Viljoen, Marinda,1968- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.